Delayed plumage maturation explains differences in breeding performance of Saffron Finches. (2nd October 2018) - Marques-Santos, Fernando; Wischhoff, Uschi; Roper, James Joseph; Rodrigues, Marcos
ABSTRACT: Theory predicts that, even within the same population, birds may vary their breeding investment with age. This may be due to an improvement in individual quality of old birds in body condition, foraging and in nesting experience. Birds commonly signal age and individual quality to potential mates and competitors through plumage colour. Young male and female breeders of Saffron Finches ( Sicalis flaveola ) have dull plumages that change to yellow with age. We asked whether older, yellow birds are in better condition and invest more in breeding than dull, younger birds. In southern Brazil, we monitored Saffron Finches breeding in nest-boxes over three breeding seasons. We found that yellow birds were in better condition: females had more furcular fat and males were heavier. Yellow parents bred earlier, had larger clutch sizes, shorter incubation periods, re-nested more and ultimately fledged twice as many offspring as dull parents. Egg mass, nestling mass and nest survival probability were similar between plumage colours. Female colour predicted clutch sizes and incubation periods better than male colour. Our results highlight the importance of accounting for female quality and reproductive investment decisions within the context of sexual selection.